2009
DOI: 10.1182/blood-2008-06-162958
|View full text |Cite
|
Sign up to set email alerts
|

A HaemAtlas: characterizing gene expression in differentiated human blood cells

Abstract: Hematopoiesis is a carefully controlled process that is regulated by complex networks of transcription factors that are, in part, controlled by signals resulting from ligand binding to cell-surface receptors. To further understand hematopoiesis, we have compared gene expression profiles of human erythroblasts, megakaryocytes, B cells, cytotoxic and helper T cells, natural killer cells, granulocytes, and monocytes using whole genome microarrays. A bioinformatics analysis of these data was performed focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
271
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 224 publications
(285 citation statements)
references
References 43 publications
11
271
2
1
Order By: Relevance
“…In addition, comparison of gene expression in human leukocytes identified DKK3 as one of the five genes uniquely expressed in CD8 T cells (26). In light of our finding, we suggest that DKK3 expression may be restricted only to subsets of tolerant CD8 T cells.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, comparison of gene expression in human leukocytes identified DKK3 as one of the five genes uniquely expressed in CD8 T cells (26). In light of our finding, we suggest that DKK3 expression may be restricted only to subsets of tolerant CD8 T cells.…”
Section: Discussionmentioning
confidence: 74%
“…A recent megakaryocyte (MK) transcriptome study (16) reported that Fzd4 and 6 were the most abundantly expressed Fzd isoforms in MKs, suggesting that these may also present in platelets. Indeed, we detected Fzd4 and 6 transcripts (Fig.…”
Section: Fzd6 Is Present and Functional In Plateletsmentioning
confidence: 99%
“…Here we performed a conservation analysis of the most differentially expressed genes in resting T, B, NK, and myeloid cells in the mouse and human at the genome-wide level (see Methods) (Chambers et al 2007;Watkins et al 2009). Our analysis revealed that among trans-membrane (TM) or secreted protein coding genes, those specifically expressed in NK cells have proportionally fewer orthologs across all vertebrates compared with other immune cells.…”
Section: Conservation Analysis Of Mammalian T- B- Nk- and Myeloidcmentioning
confidence: 99%
“…In mouse and human, many antibodies for these markers are available and can be used to isolate homogeneous immune cell populations using flow cytometry. Gene expression profiling studies of isolated immune cell populations have further allowed genome-wide identification of cell-type-specific genes (Chambers et al 2007;Watkins et al 2009;Shay and Kang 2013;Vu Manh et al 2014). These studies revealed an overall conservation of immune cells' gene expression between mouse and human ).…”
mentioning
confidence: 99%